The financial business characteristics of hand line fisheries in the SAP Area of Raja Ampat Islands and the surrounding sea : Karakteristik finansial usaha perikanan pancing ulur di Kawasan SAP Kepulauan Raja Ampat dan laut sekitarnya - Muhammad Nur Arkham; Roma Yuli F. Hutapea; Mathius Tiku; Restu Widayaka; Evi Maya Sari (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2020)
The activities of capture fisheries at The Natural Sanctuary in the Waters (SAP) area of ​​Raja Ampat Regency are mostly small-scale fisheries. The development of business the hand-line fishing gear is very important for the sustainable use of small-scale capture fisheries activities in conservation areas. The purpose of this study is to assess the feasibility of hand-line fishery business from the financial aspect and the risk of its development in the SAP area of ​​the Raja Ampat Islands and the surrounding sea. The types of data needed in this study are primary and secondary data. Data analysis used in this study includes analysis of financial parameters, investment criteria, and business risk analysis. The results showed that handline fishery business in the SAP area of ​​Raja Ampat Regency and the surrounding sea is profitable and feasible to develop. This result is seen from the analysis of the financial feasibility of the business with a profit of Rp. 9,003,171.00, the R / C ratio value of 1.11, and the payback period (PP) value of 2.95 years. In addition, it is also seen from the feasibility of investment that the value of NPV> 0, net B / C> 1, and IRR> the prevailing interest rate is 5.25%. Judging from the risk, the hand-line fishing business is categorized as not at risk to be developed. This result is seen from the value of CV (0.2) ≤ 0.5, then the value of L (8,428,400) ≥ 0, which means that the company will always profit or break even and do not experience the risk of loss.